O lekarnarju Petru Eugenu Sušnju in njegovem izvodu knjige Friedricha Wöhlerja - Fabjančič, Igor (Farmacevtski vestnik, 2022)
At the turn of the 19th and 20th centuries, Peter Eugen Sušanj was the owner of a pharmacy at Sušak (today part of Rijeka, Croatia), which offered visitors a wide range of medicines that covered contemporary materia medica. The pharmacy's offer may be followed by reading Novi list, which also contains Sušanj’s advertisements for rather exotic medicines. During his studies and probably during his professional work, he used Wöhler's book “Fundamentals of inorganic and organic chemistry”, which, based on a critical assessment, are the works of the highest quality in the field of pharmaceutical chemistry in the 19th century.
Keywords: Eugen Sušanj, Petar; Farmacija; Lekarniška dejavnost; Wöhler, Friedrich; Zgodovina